Circulating miRNAs correlate with clinical evaluation of activity in ANCA-associated glomerulonephritis - Matic Bošnjak; Željka Večerić-Haler; Živa Pipan Tkalec; Emanuela Boštjančič; Nika Kojc (European Journal of Medical Research)
Abstract Introduction Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis is an autoimmune necrotizing small vessel vasculitis, frequently resulting in severe renal manifestations such as rapidly progressive glomerulonephritis (AAV-GN). Monitoring disease activity and determining ongoing renal involvement remain significant clinical challenges due to the limitations associated with traditional biomarkers. This study focused on the potential of circulating microRNA (miRNA) as supplementary noninvasive biomarkers for disease activity in AAV-GN. Methods This prospective follow-up study involved serum samples from 60 patients with biopsy-proven AAV-GN, collected at renal biopsy and at 3-, 6-, 12-, and 24-month intervals post-biopsy. Nine miRNAs (miR-21-3p, miR-30b/d/e-5p, miR-142-5p, miR-150-5p, miR-181a-5p, miR-181b-5p, and let-7a-5p) were selected based on the differential expressions in renal tissue and corresponding serum samples identified in the previous research phases. Expression analysis was performed using quantitative real-time polymerase chain reaction and correlated with disease activity based on the Birmingham Vasculitis Activity Score and other clinical parameters. Results A significant correlation was identified between disease activity and the expression levels of the miR-30 family members and let-7a. Specifically, these miRNAs demonstrated consistent correlation patterns across follow-up samples independent of the time elapsed post-biopsy, with down-regulation correlating with the presence of active disease. Notably, the miRNA expression profile in partial remission appeared analogous to that of complete remission, suggesting that many patients categorized as having partial remission may, in fact, be considered in true clinical remission. Conclusion This study supports serum miRNA profiling as an adjunct noninvasive biomarker for assessing disease activity in AAV-GN. Such an approach could provide complementary information alongside traditional biomarkers and refine the future management of AAV-GN. However, it is important to acknowledge that our actual study cohort was small due to challenging technical aspects of miRNA expression analysis in the serum. Therefore, further research with larger cohorts is required to validate these results and assess their clinical applicability.